Wi-Fi Fingerprint Radio Map Creation by Using Interpolation. (2017) - Racko, Jan; Machaj, Juraj; Brida, Peter
Abstract: The most common answer to question what can be used for location estimation is GPS. It is not an incorrect answer, but not within buildings. Multipath propagation and attenuation by trespassing through walls makes GPS an unprecise system for indoor positioning. Therefore many different techniques have been developed. One of options is to use wireless fingerprinting. Advantage of the mentioned method is that it doesn't need additional equipment and can be built based on existing Wi-Fi infrastructure. On the other hand, drawback of the fingerprinting is process of a radio map creation, which is very time consuming. Whole space where we want to use fingerprinting must be divided into smaller areas represented by fingerprints, which consists of RSS (Received Signal Strength) measured for each area separately. In our work we focused on interpolation methods reducing time needed for radio map creation. We will measure RSS in some positions and the rest of fingerprints will be calculated by two interpolation methods, namely linear interpolation or Delaunay algorithm. Thanks to this, time needed for radio map creation is reduced and it is easier to implement fingerprinting localization method. Paper also deals with comparison of reference points in radio map created by both interpolation methods with real measurements.